Bizet - MacDonald, Hugh 1940- (Oxford Univ. Press, 2014)
Today Georges Bizet is most immediately recognized as the composer of the acclaimed opera Carmen. One of the most frequently performed operas for over a century, Carmen explores concepts such as the femme fatale and murderous jealousy with vivacity, color, and a wealth of melody. Yet it is only one act in Bizet's story. In Bizet, renowned musicologist Hugh Macdonald goes beyond the composer's most famous opera to take an in-depth look at his entire life and oeuvre
Literaturverz. S. 277 - 283
Keywords: Bizet, Georges, -- 1838-1875; Bizet, Georges -- 1838-1875; Composers -- France -- Biography; Frankreich; Biografie